Produção e composição do leite de ovelhas Santa Inês e mestiças Lacaune x Santa Inês, e biometria de seus cordeiros - Maria Izabel Carneiro Ferreira (2009)
Sheep milk influence on the appropriate growth and development of lambs at weaning and is also used as raw material by dairy industry. This research had the objective to evaluate the effects of two nutritional managements during the final period of gestation and the number of fetuses on the performance of Santa Inês ewes and their offspring, and the effect of three sheep genotypes on the performance of Santa Inês ewes and crossbred Lacaune x Santa Inês and their lambs during the first four months postpartum. In the first experiment, Santa Inês ewes and their lambs were distributed according to the nutritional management and the type of pregnancy. Difference in milk production was only observed (P<0.05) for the type of pregnancy, with the higher average of production observed in ewes that lambed twins (1,147.2 mL/day). There was an effect of the interaction of nutritional management and type of pregnancy and the postpartum weeks for some constituents of milk (P<0.05). For the development of the lambs, there was observed only the effect of age. In the second experiment, three different genotypes of sheep were used. Milk production was different (P<0.05) for the genotypes, with the highest average recorded for the ½ Lacaune ewes (1,550.8 mL/day). There was effect (P<0.05) of the genotype for some constituents of milk and for some biometric measurements of the lambs: girth, width of chest, width of rump, length of shoulder, and length and perimeter of the ham shank. The other biometric measures were influenced only by the age of the animals (P<0.05).